Application of Bayesian networks to data mining - Rod, Martin; Jiroušek, Radim; Váchová, Lucie; Vysoká škola ekonomická v Praze. Fakulta managementu (2018)
This thesis was written to data mine a data set in field of higher education, more specifically examinations of students in bachelor's study programme in one of the Czech public university. The main goal of the thesis was to use proposed Bayesian network as a data mining tool for asserting the differences between full-time and part-time study form. Four Bayesian networks were created and used for knowledge extraction. The found differences and disproportions concerning the successful completion of this particular bachelor's study programme between those study forms were determined and discussed. A definition of key success factors concerning the courses was proposed.
Vedoucí práce: Radim Jiroušek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta managementu, 2019
Obsahuje bibliografii
Rok obhajoby 2019
Keywords: dolování dat; predikční modely; Bayesova teorie; vysokoškolské studium; management [obor dipl. práce]; diplomové práce; data mining; predictive models; Bayesian theory; college study; master's theses